Ancient Chinese Medicine Herbal Formula Huanglian Jiedu Decoction as a Neoadjuvant Treatment of Chemotherapy by Improving Diarrhea and Tumor Response - Chan, Yau-Tuen; Cheung, Fan; Zhang, Cheng; Fu, Bowen; Tan, Hor-Yue; Norimoto, Hisayoshi; Wang, Ning; Feng, Yibin (Frontiers in Pharmacology, 2020)
Background: Diarrhea is the major gastrointestinal complication in cancer patients receiving chemotherapy. Prognosis and treatment of chemotherapy-induced diarrhea (CID) remain unsatisfactory. This study aims to explore an ancient Chinese Medicine herbal formula Huanglian Jiedu Decoction (HLJDD) as an adjuvant treatment of chemotherapy-induced diarrhea. Method: HLJDD extract was prepared by GMP manufacturing with quality and stability being checked. 5-fluorouracil (5-Fu) and irinotecan (CPT-11)-induced diarrhea in mice was established and pre-, co- and post-treatment of HLJDD was implemented. Mechanism of action was explored by detecting related protein expression. In addition, the effect of HLJDD on diarrhea and tumor response induced by clinical regimen FOLFOX and FOLFIRI was measured in orthotopic colorectal cancer murine model. Results: HLJDD exhibited consistent in quality and stable at 24-month storage. Pre-treatment of HLJDD, but not co-treatment or post-treatment, could significantly improve the diarrhea score, body weight loss and intestinal damage in 5-Fu- and CPT-11-treated mice. Pre-treatment of HLJDD reduced cell apoptosis in the intestine of chemotherapy-treated mice, and promoted renewal of intestinal cell wall. CD44 was predicted as the potential target of HLJDD-containing compounds in CID. HLJDD pre-treatment induced presentation of CD44-postive cells in the intestine of chemotherapy-treated mice, and initiated expression of stemness-associated genes. Transcriptional products of the downstream Wnt signaling of CD44 were elevated. Furthermore, pre-treatment of HLJDD could significantly improve the tumor response of clinical chemotherapy regimens FOLFOX and FOLFIRI in orthotopic colorectal cancer, and reduce diarrhea and intestinal damage. Conclusion: Our study suggests the potential of HLJDD as a neoadjuvant treatment of chemotherapy by improving diarrhea and tumor response.